On Solidago gypsophila and S. pringlei (Asteraceae: Astereae), rare and not so rare Mexican endemics: A multivariate study of the Tortifolia group of subsect. Triplinerviae - Semple, John C. (2016)
Nesom (1989) described Solidago gypsophila based on three collections from central Coahuila,Mexico. It is investigated here in a multivariate morphometric analysis that also includes specimens of S.altiplanities, S. altissima var. gilvocanescens, S. juliae, S. leavenworthii, S. microglossa, S. pringlei, andS. tortifolia (the informal S. tortifolia Group) in order to determine similarities among species. Becauseonly one specimen of S. gypsophila was scored, it could not be included as an a priori group but it wasincluded in the a posteriori classificatory discriminant analysis and placed in S. altissima var.gilvocanescens on the basis of upper leaf and floral traits. In a second analysis, including only S.chilensis, S. juliae, S. pringlei, and S. tortifolia, the specimen of S. gypsophila was placed a posteriori intoS. juliae, but on the basis of leaf indument traits, phyllary shape, ecology, and distribution it is acceptedhere as a distinct species. Morphological variation in S. pringlei (syn: S. muelleri) is also explored anddiscussed. Detailed illustrations of S. gypsophila and S. pringlei are presented.